The relationship between tourism, foreign direct investment, energy consumption, agriculture and economic growth: evidence from Vietnam - THAO, HOANG THI PHUONG; CUONG, LE DINH PHU; WANG, DONG; HUONG, NGUYEN THI THU; CUONG, VU MANH; TRUNG, PHAM DINH; HIEU, DINH QUOC (The journal of contemporary issues in business and government, 2021)
This research is one of the most effective studies in Vietnam using observed variables including tourism, agriculture, foreign direct investment, energy consumption and economic development in the period 1990-2019. This work affirms the role of attracting foreign investment in Vietnam in the past 20 years, from which we predict the same results in the future. The research method used ARDL (Autoregressive Distributed Lag)model, Bound Test, ECM model and Granger causality to explore the short-run, long-run and causal relationships between them. The results show that Foreign Direct Investment (FDI) positively affects economic development while energy consumption is in the opposite direction, energy consumption exists a positive relationship to agricultural development whereas tourism development exists a negative impact in terms of drought. In addition, one-way causal relations are found that FDI promotes energy consumption, economic development leads to increased energy consumption and the promotion of tourism by energy consumption. Thereby, we have given a number of solutions to increase attracting foreign investment. In addition, we have proposed to open directions for improving renewable capacity such as finding modern renewable energy sources for agriculture and tourism development. Besides, we also show that the impact of the Covid-19 pandemic globally, which has been start in progress since 2019 until now.